Pengaruh Konsumsi Ekstrak Daun Katuk Terhadap Kecukupan ASI Pada Ibu Menyusui Di Klaten - Endang Suwanti; Kuswati Kuswati (Poltekkes Kemenkes Surakarta, 2016)
Abstract: Sauropus Androgynus, Breast Milk. Mother breat Milk is good nutrition for baby. Mother breast Milk important for growing baby. To increasing mother breast milk very good consumption food this like : leaf Katu (Sauropus androgynous), leaf Ubi jalar (Ipomoea batatas), leaf kelor (Moringa oleifera), fried corn at all, Composition of leaf katuk is proteins, fats, calcium, phosphor, iron, vitamins A, B, and C. pyrrolidinone, metil pyroglutamate and p-dodesilfenol component minor. Goal research to known relationship consumption leaf katuk with breast milk sufficient, at midwife practice Independent (BPM) on Klaten area. Methods: Pre-Posts with Control Group Design. In the research researcher measure influence intervention at an eksperiment group with comparing group control. Research worked at midwife practice Independent at the January as to Juli 2015. Population in the research is all of the mother breastfeeding at midwife practice Independent (BPM) on Klaten district. Sampling methods is quota sampling with inclusive criterion normally newborn and healthy. Research at January-July 2015. Data analysis performed to describe the variable that will be studied and performed bivariate analyze to the relationship of independent and dependent variable s using the chi-square. Results research is 70 % intervention group more produced milk than control group produced milk enough 30%. Result in statistik Analice chi-square p-value =0,002.Conclusion there was significant relationship consumption extract katuk for sufficient breast milk.